Out-of-field dose and its constituent components for a 1.5 T MR-Linac. (15th November 2021) - Yang, Bin; Tang, Ka Keung; Huang, Chen-Yu; Geng, Hui; Lam, Wai Wang; Wong, Yeung Sum; Tse, Mei Yan; Lau, Ka Ki; Cheung, Kin Yin; Yu, Siu Ki
Abstract: This study aims to quantify the relative contributions of phantom scatter, collimator scatter and head leakage to the out-of-field doses (OFDs) of both static fields and clinical intensity-modulated radiation therapy (IMRT) treatments in a 1.5 T MR-Linac. The OFDs of static fields were measured at increasing distances from the field edge in an MR-conditional water phantom. Inline scans at depths of dmax (14 mm), 50 and 100 mm were performed for static fields of 5 × 5, 10 × 10 and 15 × 15 cm 2 under three different conditions: full scatter, with phantom scatter prevented, and head leakage only. Crossline scans at isocenter and offset positions were performed in full scatter condition. EBT3 radiochromic films were placed at 100 mm depth of solid water phantom to measure the OFD of clinical IMRT plans. All water tank data were normalized to Dmax of a 10 × 10 cm 2 field and the film results were presented as a fraction of the target mean dose. The OFD in the inline direction varied from 3.5% (15 × 15 cm 2, 100 mm depth, 50 mm distance) to 0.014% (5 × 5 cm 2, dmax, 400 mm distance). For all static fields, the collimator scatter was higher than the phantom scatter and head leakage at a distance of 100–400 mm. Head leakage remained the smallest among the three components, except at long distances (>375 mm) with small field size. Compared to the inline scans, the crossline scans at the isocenter showed higher doses at distances longer than 80 mm. All crossline profiles at longitudinal offset positions showed a cone shape with laterally shifted maxima. The OFD of IMRT deliveries varied with different target size. For prostate stereotactic body radiation therapy (SBRT) treatment, the OFD decreased from 2% to 0.03% at a distance of 50–500 mm. The OFDs have been measured for a 1.5 T MR-Linac. The presented dosimetric data are valuable for radiation safety assessments on patients treated with the MR-Linac, such as evaluating carcinogenic risk and radiation exposure to cardiac implantable electronic devices.